Mother’s Knowledge And Attitude Towards VIA Test For Early Detection Of Cervical Cancer At Puskesmas 5 Ilir Palembang - Naufal Fikri Ismail; Rizal Sanif; Hadrians Kesuma Putera (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Introduction. Cervical cancer ranks among the leading causes of death in women worldwide. In Indonesia, the incidence of cervical cancer is particularly high and is expected to rise further in the future. However, a lack of knowledge and fear of the VIA test may be to blame for low screening uptake. This study was conducted to learn about mother's knowledge and attitude toward the VIA test at Puskesmas 5 Ilir Palembang. Methods. This study using descriptive method with cross-sectional design. The total sample size of people who met both inclusion and exclusion criteria is 94. Sociodemographic information, such as education, age, and employment status, is gathered through questionnaires. Results. The results of a study comparing mothers' knowledge and attitudes toward the IVA test by gender with different levels of education found that mothers' knowledge and attitudes were distributed more evenly among those with higher levels of education. Distribution of mothers' knowledge and attitudes toward the VIA test by age, those between the ages of 35 and 44 reported having low knowledge (17%) and low attitude (20%). Based on the distribution of mothers' knowledge and attitudes about the VIA test by occupation, it showed that homemakers fared worse, with fewer than 32 people possessing the necessary level of knowledge and only 28 mothers displaying the necessary level of attitude. Conclusion. Respondents between the ages of 35 and 44 with a secondary school education and a job as a mother in the home have a lower-than-average distribution of knowledge and values.